The Post-Conflict Environment Investigation and Critique - Monk, Daniel Bertrand (University of Michigan Press, 2014)
In case studies focusing on contemporary crises spanning Africa, the Middle East, and Eastern Europe, the scholars in this volume examine the dominant prescriptive practices of late neoliberal post-conflict interventionsâ€"such as statebuilding, peacebuilding, transitional justice, refugee management, reconstruction, and redevelopmentâ€"and contend that the post-conflict environment is in fact created and sustained by this international technocratic paradigm of peacebuilding. Key international stakeholdersâ€"from activists to politicians, humanitarian agencies to financial institutionsâ€"characterize disparate sites as â€œweak,â€_x009d_ â€œfragile,â€_x009d_ or â€œfailedâ€_x009d_ states and, as a result, prescribe peacebuilding techniques that paradoxically disable effective management of post-conflict spaces while perpetuating neoliberal political and economic conditions.